The Application of GPS Visitor Tracking Implications for Interpretation at Heritage Sites. Issue 1 (April 2019) - Sharp, Ryan L.; Cable, Ted T.; Burns, Aubrey
This paper presents the results of the application of GPS Visitor Tracking (GVT) to evaluate visitor movements through a heritage site. This method provides temporal and spatial distribution and "heat maps" that depict visitor movements through the site. Documenting these visitor movements indicates to interpreters where to concentrate interpretive efforts and identifies opportunities to strategically encourage visitation to less visited areas of the site. The research team approached 117 travel parties and 106 elected to participate in the study, yielding a 90.6% response rate. Analysis revealed that visitors typically travel in a clockwise direction once they entered the park, stopping at a point of interest then proceeding to the visitor center. However, the density maps revealed that other points of interest were less visited. This information about temporal and spatial distribution of visitors can provide information for creating interpretive programs that people may engage with at the park.